Dampak Penyuluhan Terhadap Tingkat Pengetahuan dan Tingkat Konsumsi Pada Penyelenggaraan Makanan di SD Islamic Global School Malang - Lintang Mega Pertiwi; Dwie sulistyorini; Theresia Puspita (Jurnal Pendidikan Kesehatan, 2019)
Many elementary schools do not have a standard portion and allow their students to take their own food so that each student eating portion varies according to student desires. Education and knowledge should be given to students so that they can raise awareness in themselves about the importance of applying a meal portion that is in accordance with the recommended portion standards and nutrients for their body. This type of research is a pre experimental study with one group pretest posttest design. The results showed that there were differences in the level of knowledge before and after nutritional education due to lecture education methods and participants could draw the attention of respondents and stimulate respondents to receive the information provided. There is no difference in the level of consumption of energy, protein, and fat before and after nutritional education, while the level of carbohydrate consumption experiences a difference before and after nutritional education.